Purwarupa Sistem Pemantauan dan Pengendalian Pertumbuhan Tanaman Cabai dalam Screen House - Edwin Phill Tenda; Andrew Lengkong; Reymon Rotikan; Stenly Adam (Fakultas Ilmu Komputer, Universitas Klabat, 2022)
Chili (Capsicum annuum L.) is a well-known spice plant and is loved because of its distinctive spicy taste. In addition, chili also contains good nutrients including vitamins A, B, C, E, potassium, phosphorus, calcium, folate, antioxidants, protein, and anti-cancer substances. Chili cultivation provides good economic potential because market demand is stable and even increases in certain seasons. One of the chili planting methods is by using a screen house which allows farmers to better control various growth parameters. In this study, an IoT-based monitoring and control system for chili plant growth parameters was developed using a Raspberry Pi, sensors, and other electronic devices. Growth parameter data is processed and sent to an online server and then presented with a time series-based visualization.